Management and Leadership Requirements in Hospital Service Supply Chain: A Mixed Method Study - Musarreza Mohagheghnejad; Amir Ashkan Nasiripour; Ruhollah Zaboli; Hossein Damghanian (Rāhburdhā-yi Mudīriyyat dar Niẓām-i Salāmat, 2024)
Background: The supply chain of hospital services is a relatively new and highly challenging field, and it is crucial for relevant officials to possess the necessary skills. The success in this domain relies on the characteristics of managers, their management practices, and their leadership style. This study aims to investigate the requirements of management and leadership in hospital services’ supply chain. Methods: This study employed a two-stage mixed-methods approach carried out from 2018 to 2021. In the first stage, a qualitative study was conducted using purposive sampling and semi-structured in-depth interviews with 15 experts in various leadership positions. The data collected in this stage were analyzed using framework approach. Subsequently, the primary themes that emerged from the analysis were presented to 8 experts  in the form of a questionnaire. The experts' responses were then analyzed to determine the level of agreement on different topics using Delphi method, Kendall's coefficient of agreement, and the mean was compared through SPSS 21. Results: The experts identified transformationalism, planning capability, crisis management, and creativity as the most crucial factors. Furthermore, there was a high level of agreement regarding the influence of managers (4.62 ± 0.51), maintaining distance from mundane routines (4.50 ± 0.53), and attending to various incidents in hospital services supply chain (4.50 ± 0.53). Considering that Kendall Rank Correlation Coefficient (w) was 0.53 in the first round and 0.72 in the second round and was statistically significant, there was a strong consensus among the expert panel. Conclusion: According to the results of the present study, it is necessary to pay serious attention to the change in management style and hospital services supply chain, there should be a special focus on the possibility of occurrence or impact of sudden accidents. Also, routine and ineffective actions should be eliminated and the managers and employees should be more creative to improve this chain. Transformational leaders should try to manage the hospital services supply chain by forming specialized teams and using the capabilities of employees with the reasonable use of financial resources and appropriate infrastructures, including information technology.